Effectiveness of anti-epidemic measures on ensuring indoor air quality of cleanrooms in a tertiary care hospital - Fedor, Lukáš; Nakládalová, Marie; Štěpánek, Ladislav; Holý, Ondřej; Matoušková, Ivanka (Central European journal of public health, 2022)
OBJECTIVES: Maintaining cleanrooms in a hospital is a key part of preventing healthcare-associated infections (HAIs). The aim of this work was to verify the effectiveness of anti-epidemic measures to ensure air quality in cleanrooms in a tertiary care hospital. METHODS: The study was based on the application of anti-epidemic measures and verification of their effectiveness by regular indoor air monitoring between the years 2014-2019. Monitoring was performed according to a recommended procedure based on European standards for cleanrooms. RESULTS: The results demonstrate a reduction in the number of airborne particles and the number of colonies, as well as the elimination of fungi and conditioned pathogens in air samples. CONCLUSIONS: The authors emphasize the importance of established anti-epidemic measures and regular monitoring for the prevention of HAIs.
Keywords: houby; monitorování životního prostředí; cleanrooms; znečištění vzduchu ve vnitřním prostředí; Air Microbiology; healthcare-associated infection; monitoring of the indoor environment; Environmental Monitoring; Cross Infection; microbial flora; Fungi; Air Pollution, Indoor; Tertiary Care Centers; Humans; mikrobiologie vzduchu; airborne dust particles; centra terciární péče; infekce spojené se zdravotní péčí; lidé